Collisions in a gas-rich white dwarf planetary debris disc. Issue 1 (21st June 2021) - Swan, Andrew; Kenyon, Scott J; Farihi, Jay; Dennihy, Erik; Gänsicke, Boris T; Hermes, J J; Melis, Carl; von Hippel, Ted
ABSTRACT: WD 0145+234 is a white dwarf that is accreting metals from a circumstellar disc of planetary material. It has exhibited a substantial and sustained increase in 3–5 $μ$ m flux since 2018. Follow-up Spitzer photometry reveals that emission from the disc had begun to decrease by late 2019. Stochastic brightening events superimposed on the decline in brightness suggest the liberation of dust during collisional evolution of the circumstellar solids. A simple model is used to show that the observations are indeed consistent with ongoing collisions. Rare emission lines from circumstellar gas have been detected at this system, supporting the emerging picture of white dwarf debris discs as sites of collisional gas and dust production.